Plain packaging of tobacco products: Lessons for the next round of implementing countries - Allwright, Shane (My University, 2020)
Plain packaging addresses the obligations to implement effective packaging and labelling measures under Article 11 of the WHO Framework Convention on Tobacco Control (FCTC) and to comprehensively ban tobacco advertising, promotion and sponsorship under FCTC Article 13. There is no need for countries to reinvent the wheel; they can follow the example of other countries with regard to the wording of their legislation as well as arguments and strategies to counteract tobacco industry opposition. There are also valuable resources that countries can use, including plain packaging evidence summaries and toolkits such as the Campaign for Tobacco-Free Kids’ Plain Packaging Toolkit, WHO’s report on the evidence, design and implementation of tobacco product plain packaging17, and Cancer Council Victoria’s Plain Facts. While legal challenges against plain packaging have been unsuccessful, great care is nonetheless required in drawing up legislation. Those involved in drafting plain packaging legislation should work with lawyers and others with experience in countries that have already enacted plain packaging to ensure that their plain packaging legislation is strong and that potential loopholes are minimized.Plain packaging has great potential globally to change societal perceptions and thereby denormalise use of tobacco products especially among youth, who are vulnerable to tobacco industry marketing strategies. This is particularly important in LMICs where the tobacco industry is aggressively marketing their products. Many LMICs therefore have a unique opportunity to prevent further growth of the tobacco epidemic through plain packaging along with other evidence-based tobacco control measures. It is now time for all countries to move forward with tobacco plain packaging to help save lives by reducing tobacco-related death and disease.
PUBLISHED
DOI: https://doi.org/10.18332/tid/130378
Keywords: plain packaging, tobacco products, standardized packaging, tobacco control policy, low and middle income countries; Health policy